Shedding light on the fundamental mechanism underlying hypnotic analgesia - Keppler, Joachim (Annals of Palliative Medicine, 2017)
Owing to the increasing importance of clinical hypnosis in pain therapy and palliative care, there is a growing interest in uncovering the mechanism underlying hypnotic analgesia. The neurophysiological findings suggest that the hypnotic state is associated with an altered operating mode of the brain that is clearly different from the normal operating mode. While in the normal operating mode a dolorogenic stimulus induces a highly synchronized large-scale activity pattern that leads to the experience of pain, the altered operating mode inhibits the synchronization of spatially divided brain regions. As a consequence, the con-scious experience of pain cannot arise. In order to gain a deeper understanding of the mechanism, a novel theoretical framework is made use of. It accepts consciousness as a fundamental property of the universe and is based on the hypothesis that the whole range of phenomenal qualities is built into the frequency spectrum of a ubiquitous background field. The body of evidence supports the view that in the normal operating mode our brains act as filters that extract the plethora of phenomenal nuances selectively from this field. In the altered operating mode, which establishes under hypnotic conditions, the extraction of phenomenal qualities is partially prevented. From this perspective, hypnotic analgesia is due to an impairment of the fundamental mechanism underlying conscious perception.